[PP.16.08] HYPERTENSIVE DIABETIC AND THE INCIDENCE OF CARDIOVASCULAR OUTCOMES AND COMMITMENT RENAL IN ELEVEN YEARS OF HISTORICAL COHORT. (September 2016) - Sousa, A.C.; Neiva, T.C.; Magalhães, F.; Jardim, T.; Jardim, P.C.; Barroso, W.; Moreira, H.; Souza, H.; Costa, T.; Rezende, L.; Montello, M.; Araújo, Y.C.; et al.
Abstract : Objective: To identify non-lethal cardiovascular outcomes and indicative of decrease of kidney function in a cohort of diabetic and non-diabetic hypertensive type 2 in regular and continuous treatment in a specialized center for hypertensive patients. Design and method: Historical cohort of diabetic hypertensive (exposed group) and nondiabetic (unexposed group) in regular treatment for at least 11 years in a reference center for hypertension treatment. Initial cohort assessment in 2004, with intermediate follow-up in 2009 and final follow-up in 2015; variables studied: gender, race, age, blood pressure, body mass index, glycated hemoglobin, duration of hypertension diagnosis, diabetes and specialized treatment, non-fatal cardiovascular events, indicative of decrease in renal function using creatinine clearance. For the variables association analysis was used chi-square test or Fisher's exact, at a 5% significance level. Results: Included 139 hypertensive patients (diabetics: 55; nondiabetic: 84), with a mean time of hypertension treatment at the first analisis of 6 years. Most patients were females(75.5%) and the white race was predominant (55.8%). Initially the average overall age was 57.4 years, similar in both groups. In eleven years, the exposed group had a higher risk of being affected by acute myocardial infarction(12.2 times), stroke(6.1 times more) and hospital admissions (2.2 times) compared to the unexposed. The diabetes diagnosis time in this cohort was not associated with the incidence of the analyzed events. Also the exposed group had 2.3 times greater risk to not controll the blood pressure. Regarding kidney function the exposed group decreased more significantly creatinine clearance. They started with 82, 9 min/1.73 m 2 and finished with 64, 2 min/1.73 m 2 and the unexposed group began with 70, 2 min/1.73 m 2 and finished 61, 9 min /1.73 m 2 (p < 0.05). Categorizing the glomerular filtration rate to <60 min/1.73 m 2 and >/=60 min/1.73 m 2 there was no major loss of renal function in diabetic patients since they had at the end renal injury rates of 43.4% and 45.2% nondiabetic (p > 0.05). Conclusions: Hypertensive diabetics had higher chance to be affected by cardiovascular outcomes compared to non-diabetic patients in this cohort. Hypertensive diabetics has an increas risk for the occurrence of cardiovascular outcomes, thereby this population requires more intensive actions to minimize health hazards.